(untitled) ("Conference on Universal Science Research 2023", 2025)
Vocabulary development is one of the most crucial yet challenging aspects of foreign language acquisition. Many English Language learners struggle to memorize new words or identify a number of meanings that terms hold based on diverse contexts. Contextual clues and hints surrounding unfamiliar words in sentences or paragraphs are great assets for learners in inferring meanings and support both vocabulary retention and comprehension. This article is devoted to analyzing findings from well-known international scholars, including British, American, Chinese, and Finnish researchers, to explore the impact of contextual learning on vocabulary development.